Characteristics of Anisometropic Patients with and without Strabismus - Reşat Duman; Huban Atilla; Emine Çatak (Türk Oftalmoloji Dergisi)
Objectives: To evaluate the risk factors for strabismus in patients with anisometropia by comparing degree of anisometropia, depth of amblyopia, and binocular visual function in anisometropic patients with and without strabismus. Materials and Methods: Sixty-five anisometropic patients older than 5 years with amblyopia in one eye who were followed in the Ankara University Faculty of Medicine, Department of Ophthalmology, Pediatric Ophthalmology and Strabismus Unit between May 2009 and April 2010 were included in this study. There were 27 cases of strabismus. The depth of amblyopia, degree of anisometropia, and binocular visual function were assessed in anisometropic cases with and without strabismus. Results: The 65 patients with anisometropia were divided into two groups: 27 patients with strabismus (group 1) and 38 patients without (group 2). Depth of amblyopia was greater in patients with strabismus compared to those without (p=0.006). In patients with strabismus, there was no correlation between angle of deviation and depth of amblyopia (p=0.453). In anisometropic amblyopia patients without strabismus, there was a positive correlation between depth of anisometropia and depth of amblyopia (p=0.35, Pearson’s correlation coefficient=0.343). Comparison in terms of anisometropia showed that patients with strabismus had significantly larger spherical difference between the two eyes than in patients without strabismus (p=0.000, Mann-Whitney U test). There was no significant difference in terms of cylindrical values (p=0.146, Mann-Whitney U test). There was no statistically significant difference in the presence of fusion between anisometropic patients with and without strabismus. Conclusion: The risk of developing strabismus increased as degree of anisometropia increased in anisometropic cases. In addition, depth of amblyopia was greater in anisometropic patients with strabismus.